Respostas
respondido por:
2
Resposta:
e) x = 15
f) y = 3
g) n = 9
h) a = 27
Explicação passo-a-passo:
e) 6x - 19 = 71
6x = 71 + 19
6x = 90
x = 90 / 6
x = 15
f) 2y + 4 = 10
2y = 10 - 4
2y = 6
y = 6 / 2
y = 3
g) 9n - 36 = 45
9n = 45 + 36
9n = 81
n = 81 / 9
n = 9
h) 3a + 10 = 91
3a = 91 - 10
3a = 81
a = 81 / 3
a = 27
Espero ter ajudado ;)
liviadiasleandro46:
ajudou mt obrigado
respondido por:
0
E) 6x-19=71
6x=71+19
6x=90
x=90/6
x=15
F)2y+4=10
2y=10-4
2y=6
y=6/2
y=3
G)9n-36=45
9n=45-36
9n=9
n=9/9
n=1
H)3a+10=91
3a=91-10
3a=83
a=81/3
a=27
6x=71+19
6x=90
x=90/6
x=15
F)2y+4=10
2y=10-4
2y=6
y=6/2
y=3
G)9n-36=45
9n=45-36
9n=9
n=9/9
n=1
H)3a+10=91
3a=91-10
3a=83
a=81/3
a=27
Perguntas similares
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás